Kritik Sosial dalam Musik: Studi Kasus Lagu Realita Karya Fourtwnty - Moses Christian Almas; Oktori Stenly Merang; Aan Surya Payunglangi; Erik Jeansen (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2022)
Fourtwnty Music Group is an Indie music genre. This music group creates songs that are about life and some are about criticism, and this band is very popular with young people but not many understand the lyrics of every song that he creates. This study aims to examine a work of art, especially in our report on the song Realita created by the group band Fourtwnty, in which every work he creates conveys deep meaning to many people. The method we use in our research is using a qualitative method. And as for our conclusion on our criticism, namely how the song Reality conveys a message to many people through songs that are very characterized and classy. The fourtwnty music group has inspired many young musicians with their works and words. And from all of Fourtwnty’s works, he dedicates his music to spread the message of tolerance, peace and pluralism.